Deconstructing Neurogenesis, Transplantation and Genome-Editing as Neural Repair Strategies in Brain Disease - Chohan, Muhammad O. (Frontiers in Cell and Developmental Biology, 2020)
Neural repair in injury and disease presents a pressing unmet need in regenerative medicine. Due to the intrinsically reduced ability of the brain to replace lost and damaged neurons, reversing long-term cognitive and functional impairments poses a unique problem. Over the years, advancements in cellular and molecular understanding of neurogenesis mechanisms coupled with sophistication of biotechnology tools have transformed neural repair into a cross-disciplinary field that integrates discoveries from developmental neurobiology, transplantation and tissue engineering to design disease- and patient-specific remedies aimed at boosting either native rehabilitation or delivering exogenous hypoimmunogenic interventions. Advances in deciphering the blueprint of neural ontogenesis and annotation of the human genome has led to the development of targeted therapeutic opportunities that have the potential of treating the most vulnerable patient populations and whose findings from benchside suggest looming clinical translation. This review discusses how findings from studies of adult neurogenesis have informed development of interventions that target endogenous neural regenerative machineries and how advances in biotechnology, including the use of new gene-editing tools, have made possible the development of promising, complex neural transplant-based strategies. Adopting a multi-pronged strategy that is tailored to underlying neural pathology and that encompasses facilitation of endogenous regeneration, correction of patient’s genomic mutations and delivery of transformed neural precursors and mature disease-relevant neuronal populations to replace injured or lost neural tissue remains no longer a fantasy.